Serial Assessment of Gray Matter Abnormalities after Sport-Related Concussion - España, Lezlie Y.; Lee, Ryan M.; Ling, Josef M.; Jeromin, Andreas; Mayer, Andrew R.; Meier, Timothy B. (Journal of neurotrauma, 2017)
There is an urgent need to characterize the acute physiological effects of sport-related concussion (SRC). We investigated the effects of SRC on gray matter structure and diffusion metrics in collegiate athletes at 1.64 (T1; n = 33), 8.33 (T2; n = 30), and 32.15 days (T3; n = 36) post-concussion, with healthy collegiate contact-sport athletes serving as controls (HA; n = 46). Plasma levels of glial fibrillary acidic protein (GFAP) were assessed in a subset of athletes. We hypothesized that acute SRC would be associated with increased fractional anisotropy (FA), decreased mean diffusivity (MD), and increased GFAP relative to noninjured HA, without acute differences in gray matter volume or cortical thickness. Further, we hypothesized that neither diffusion nor structure would show longitudinal changes across the first month post-SRC. Finally, we hypothesized that gray matter diffusion metrics would correlate with plasma GFAP levels, as indicated by pre-clinical literature. Consistent with our hypothesis, acute SRC was associated with decreased MD in the left pallidum, increased FA in the right amygdala, and a significantly greater number and volume of subject-specific clusters with increased FA compared to HA. No differences in gray matter volume, cortical thickness, or GFAP were observed between groups. There were no longitudinal changes in any measure across the first month post-SRC. Finally, FA in the right amygdala was inversely correlated with GFAP at T2. These results suggest that gray matter diffusion metrics may be useful in determining the physiological effects of SRC.